2011
DOI: 10.1177/0963947011398281
|View full text |Cite
|
Sign up to set email alerts
|

‘The Blaydon Races’: lads and lasses, song tradition, and the evolution of an anthem

Abstract: In this article I examine the evolution of the Tyneside song, 'The Blaydon Races', into a local anthem, with a focus on the contribution of the plurals lads and lasses to this status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Originally written in the 1860s by the music-hall artist George 'Geordie' Ridley, this song has endured to become the anthem of JOAN BEAL is Professor of English Language at the University of Sheffield. Hermeston (2011) found that, in a corpus of 285 Tyneside songs from the nineteenth century, the words that most frequently collocated with lads were lasses and Tyneside, indicating a strong indexical link between the words lads and lasses and local identity. Her publications include English in Modern Times (Arnold 2004) and (with Philip Shaw) the revised and updated second edition of Charles Barber's The English Language: a Historical Introduction (CUP 2009 Tyneside and its chorus is sung by fans of Newcastle United Football Club (Beal, 2000;Hermeston, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Originally written in the 1860s by the music-hall artist George 'Geordie' Ridley, this song has endured to become the anthem of JOAN BEAL is Professor of English Language at the University of Sheffield. Hermeston (2011) found that, in a corpus of 285 Tyneside songs from the nineteenth century, the words that most frequently collocated with lads were lasses and Tyneside, indicating a strong indexical link between the words lads and lasses and local identity. Her publications include English in Modern Times (Arnold 2004) and (with Philip Shaw) the revised and updated second edition of Charles Barber's The English Language: a Historical Introduction (CUP 2009 Tyneside and its chorus is sung by fans of Newcastle United Football Club (Beal, 2000;Hermeston, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Her publications include English in Modern Times (Arnold 2004) and (with Philip Shaw) the revised and updated second edition of Charles Barber's The English Language: a Historical Introduction (CUP 2009 Tyneside and its chorus is sung by fans of Newcastle United Football Club (Beal, 2000;Hermeston, 2011). Originally written in the 1860s by the music-hall artist George 'Geordie' Ridley, this song has endured to become the anthem of JOAN BEAL is Professor of English Language at the University of Sheffield.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations